Method for rapidly preparing TiB2-TiN-based metal ceramic based on 3D printing and SHS compounding
Through the combination of 3D printing and SHS composite process, CoCrFeMnNiX high-entropy alloy is used as the metal bonding phase, which solves the problem of difficult preparation of TiB2-TiN ceramics in complex shape structures and insufficient high-temperature strength and toughness, and realizes TiB2-TiN ceramics with excellent high-temperature strength and toughness The batch preparation is rapid, and the material performance is significantly improved.
Patent Information
- Application Number
- CN202310954955.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2024-12-20
AI Technical Summary
It is difficult to quickly prepare TiB2-TiN metal cermets with complex shape structures in batches, and their high temperature and toughness are insufficient, and the high sintering temperature leads to irregular grain growth and metal bonding phase deformation.
Using 3D printing and SHS composite technology, combined with reaction hot press sintering, using CoCrFeMnNiX high-entropy alloy as metal bonding phase, to achieve rapid batch preparation of TiB2-TiN ceramics, reduce sintering temperature and increase material Density and toughness.
It has achieved rapid batch preparation of TiB2-TiN ceramics with excellent high-temperature strength and toughness. The room temperature hardness reaches 17-18GPa, the bending strength reaches 600-750MPa, and the fracture toughness reaches 6-8MPa·m1/2. The hardness at 1000℃ is ≥9GPa, and the resistance is resistant to The bending strength is ≥500MPa, the fracture toughness is ≥5MPa·m1/2, and the material grains are small and the particles are evenly distributed.
Smart Images

Figure CN119159090A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal ceramic material preparation, and specifically relates to a method for rapidly batch preparing TiB2-TiN based metal ceramics with complex structures and shapes based on 3D printing and SHS composite. The metal ceramic material prepared by the method has outstanding wear resistance and toughness. Background Art
[0002] TiB2 ceramic is an extremely stable superhard ceramic material. Its melting point is as high as 3225℃ and its hardness is HV30-40GP. It has stable chemical properties and strong corrosion resistance. In addition, it has good electrical conductivity and high-temperature mechanical properties. Therefore, it is widely used in cutting tools, wear-resistant parts, and electrode fields. However, TiB2 has a low self-diffusion coefficient and poor sintering performance, resulting in low high-temperature oxidation resistance, thermal shock resistance, and fracture toughness values, which limits its application. In order to further improve the strength and toughness of TiB2 ceramics and meet the needs of industrial production, researchers have developed a TiB2-TiN composite ceramic material system with excellent mechanical properties and wear and corrosion resistance, which has attracted the attention of developers. At the same time, in order to promote material densification and improve mechanical properties, some scholars have increased wettability by adding metal sintering aids, including Ni, Co, and high entropy alloys, thereby reducing the sintering temperature of metal ceramics. Appropriate TiN and metal binder phase content can improve TiB2 grain boundary strength and material density, thereby achieving the purpose of improving the strength and toughness of TiB2-TiN-based metal ceramics at the same time.
[0003] At present, the traditional molding method of TiB2-TiN-based cermets is mainly based on powder metallurgy pressing or extrusion followed by sintering, which mainly includes the following processes: 1. Hot pressing sintering. It is a sintering method that fills dry powder into the mold, and then presses and heats it in a uniaxial direction to complete molding and sintering at the same time. The research of Gao Jie et al. (Gao Jie, Song Jinpeng, Liang Guoxing, et al., Tool Technology, 2017) shows that with the help of hot pressing sintering, with Ni as the metal binder phase and carbon fiber as the reinforcement phase, the bending strength of TiB2-TiN-based cermets can reach 738±21MPa, and the fracture toughness is as high as 12.07±0.3MPa·m 1 / 2, hardness is 19±0.6GPa. While obtaining high strength and toughness, it can also improve high-temperature mechanical properties. 2. Reaction hot pressing sintering (SHS). It is a material preparation process developed by combining combustion synthesis with hot pressing sintering technology. Liu (MMLiu, MHHu, YYWang, et al, Ceramics International, 2021) et al. used Ti and BN as raw materials to synthesize TiB2-TiN ceramic composite materials at 5.0GPa gas pressure and 1400-1800℃ high temperature. Its relative density reaches 96.2%, and its maximum hardness is as high as HV 17.9GPa. However, due to the limitations of molds and forming conditions, the above two methods are difficult to quickly batch prepare complex-shaped structural parts. At the same time, the sintering temperature of the composite ceramic material prepared by reaction hot pressing without adding a metal binder phase is too high, and the grains grow irregularly and abnormally, which greatly reduces the mechanical properties of the material. In addition, when used at high temperatures, the Ni metal binder phase is prone to deformation and even creep.
[0004] Binder jet 3D printing technology has huge cost and efficiency advantages in the large-scale mass production of complex-shaped structural materials, and has therefore received attention from the automotive, cutting tool and other industrial fields in recent years. CoCrFeMnNiX high entropy alloy has a single FCC face-centered cubic structure and has high strength and plasticity at both high and low temperatures, which has attracted much attention. In summary, how to use appropriate molding methods to prepare TiB2-TiN-based cermets with CoCrFeMnNiX high entropy alloy as the metal binder phase is of great significance. Summary of the invention
[0005] In view of the problems existing in the prior art, the purpose of the design of the present invention is to overcome the difficult problems of difficult preparation of complex shape structures and insufficient high-temperature toughness of TiB2-TiN metal ceramics, and to provide a preparation method for TiB2-TiN-based metal ceramics with CoCrFeMnNiX high entropy alloy as the metal bonding phase, which can be used for rapid batch preparation of complex shape structures and has both high-temperature strength and toughness. By adopting the technical scheme of the present invention, the TiB2-TiN-based metal ceramic materials produced rapidly in batches have good high-temperature strength and toughness, and can be used for the industrial production of metal ceramic tools, parts and components and electrode materials with complex shape structures.
[0006] This is achieved specifically through the following technical solutions:
[0007] A method for rapidly preparing TiB2-TiN-based cermets based on 3D printing and SHS composite, characterized in that the method comprises the following steps:
[0008] 1) Weigh the raw materials of TiB2-TiN-based cermet in proportion, place them in a double J-blade mixing and vibrating integrated machine for mixing, and obtain a bonded jet 3D printing mixture after the mixing is completed;
[0009] 2) loading the mixture prepared in step 1) together with the binder into a binder jet 3D printer, setting printing and slicing parameters according to the three-dimensional models of parts with different complex shapes, and performing infrared curing to obtain a TiB2-TiN-based metal ceramic material body;
[0010] 3) transporting the TiB2-TiN-based metal ceramic material green bodies obtained in step 2) in batches to a gas pressure sintering furnace, completing degreasing + HIP gas pressure sintering to obtain rough parts;
[0011] 4) The rough component samples obtained in step 3) are subjected to batch double-end surface grinding and polishing to finally obtain TiB2-TiN metal ceramics with complex shape structures.
[0012] In the above steps, by combining the bonding jet 3D printing technology, the reasonable proportion of the reaction raw material components and the hot pressing sintering process, the performance of TiB2-TiN-based metal ceramics can be quickly prepared in batches and optimized to obtain high-temperature toughness; with the help of the bonding jet 3D printing technology, the complex shape structural parts of TiB2-TiN-based metal ceramics can be formed by droplet injection and powder bonding. At the same time, the short-term high heat release of the in-situ synthesis reaction in the hot pressing sintering process promotes the volatilization of the residual binder in the powder, reduces the sintering temperature, and thus prepares high-performance TiB2 composite ceramics; in addition, the radius difference δ of CoCrFeMnNiX (X = Al, Ti, V, Si, etc.) high entropy alloy is small, presents a FCC single-phase structure, and has excellent comprehensive performance. It can wet TiB2-TiN composite ceramics while also improving the toughness of metal ceramics in a high-temperature environment. The above advantages are combined to achieve high toughness and batch rapid preparation of complex shape structure TiB2-TiN-based metal ceramic materials.
[0013] Furthermore, in step 1), the raw materials include Ti, BN, and CoCrFeMnNiX high entropy alloy, and the mass proportion of each raw material is: Ti: 60-70wt%, BN: 20-25wt%, CoCrFeMnNiX: 10-15wt%.
[0014] Furthermore, the X element selected radius difference δ of the CoCrFeMnNiX high entropy alloy is less than 12%, such as V: 5.06%, Ti: 11.4%, Ti: 11.53%, etc.
[0015] Furthermore, in step 1), the double J-blade mixing and vibrating integrated machine adopts a semicircular rocking block with a vibration amplitude of ≤3°, the blades are in a double J shape, and dual power drive is used to achieve forward and reverse rotation; the loading capacity of the integrated machine: 50%≤loading capacity≤80%, and the coefficient of variation CV of the uniformity of the mixture is ≤5%.
[0016] Further, in step 2), the binder mainly comprises the following components in percentage by weight: propylene resin: 55-85wt%, acrylate reactive diluent: 15-35vol%, photoinitiator: 1-5vol%, up-conversion material: 1-5vol%, the addition amount of the binder accounts for 35-45wt% of the mixture, and each layer of the binder is infrared cured after spraying, the infrared wavelength is 800-980nm, and the infrared radiation power is 30-80W·cm -2 .
[0017] Furthermore, the acrylic resin is selected from at least one of polyurethane acrylate, amino acrylate, and epoxy acrylate; the acrylate reactive diluent is selected from at least one of 1,6-hexanediol diacrylate, pentaerythritol triacrylate, and tripropylene glycol diacrylate.
[0018] Furthermore, the photoinitiator is selected from at least one of sodium dodecyl sulfate, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and 2-hydroxy-2-methyl-1-phenylacetone; the up-conversion material is selected from at least one of fluoride, oxide, and oxygen-containing acid salt; the fluoride is at least one of NaYF4, NaErF4, NaGdF4, LuF3, and CaF3; the oxide and oxygen-containing acid salt are at least one of LaPO4, PbWO4, and GdVO4.
[0019] Further, in step 3), the specific process of degreasing + HIP gas pressure sintering is: room temperature-200°C, 2-3°C / min; 200°C-200°C, keep warm for 30-60min; 200-350°C, 1-2°C / min; 350-350°C, keep warm for 60-90min; 350-500°C, 1-2°C / min; 500-500°C, keep warm for 90-120min; 500-1000°C, 5-10°C / min; 1000-1400°C, 3-5°C / min; 1400-1400°C, keep warm for 60-90min; 1400-500°C, 10°C / min; cooling with the furnace; HIP gas pressure process: 0-1000°C, 0MPa; 1000-1400°C, 5-8MPa; then depressurize.
[0020] Furthermore, in step 4), the surface parallelism of the component after grinding and polishing reaches 0.002 mm, the surface roughness can reach up to Ra0.4 μm, and the workpiece size deviation is ±0.002 mm.
[0021] In the above process, binder jet 3D printing can be used to batch produce parts with complex shapes and structures. At the same time, with the help of in-situ reaction hot pressing sintering process, TiB2-TiN-based metal ceramics can be obtained by relying on rapid reaction and uniform densification under gas pressure.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1) A method for rapidly preparing TiB2-TiN-based cermets by bonding jet 3D printing and SHS composite of the present invention can batch prepare TiB2-TiN-based composite cermets with complex shape structures and excellent high-temperature toughness; X-ray diffraction (XRD) and scanning electron microscopy (SEM) analysis of the material show that the crystal phase of the material obtained by the present invention is TiB2, TiN and FCC structural bonding phase, the grains are fine (500-600nm), and the particles are evenly distributed TiB2-TiN-based cermets;
[0024] 2) A method for rapidly preparing TiB=-TiN-based cermets by bonding spray 3D printing and SHS composite of the present invention, wherein the prepared material has a room temperature hardness of 17-18 GPa, a bending strength of 600-750 MPa, and a fracture toughness of 6-8 MPa·m 1 / 2 , at 1000℃, hardness ≥9GPa, flexural strength ≥500MPa, fracture toughness ≥5MPa·m 1 / 2 .
[0025] 3) The method of the present invention for rapidly preparing TiB2-TiN-based metal ceramics by combining bonded jet 3D printing and SHS has the possibility of rapidly preparing TiB2-TiN-based metal ceramic parts with complex shapes in batches, shortening the production time of materials and achieving the possibility of manufacturing parts with complex shapes. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the XRD pattern of the TiB2-TiN based cermet prepared in Example 1 of the present invention;
[0027] Figure 2 The polished surface SEM image and particle size distribution image of the TiB2-TiN based cermet prepared in Example 1 of the present invention;
[0028] Figure 3 Polishing surface SEM image and particle size distribution diagram of the TiB2-TiN based cermet prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with specific embodiments to facilitate a better understanding of the present technical solution.
[0030] Embodiment 1: A method for rapidly preparing TiB2-TiN-based cermets by bonding jet 3D printing and SHS, comprising the following steps:
[0031] Step 1: Weigh the binder jet 3D printing raw materials, with a ratio of Ti: 64wt%, BN: 22wt%, CoCrFeMnNiTi: 14wt%. Then place the materials in a double J-blade mixing and vibrating machine with a loading capacity of 75% and a mixing time of 12h. After the mixing is completed, a mixture with a coefficient of variation CV of 3.6% is obtained;
[0032] Step 2: Load the mixture and binder into the binder jet 3D printer, the binder content is 35wt% of the premix. The binder ingredients are: amino acrylate 60vol%, 1,6-hexanediol diacrylate 30vol%, sodium dodecyl sulfate 5vol%, NaErF4:Tm 3 5vol%. The thickness of the mixture and adhesive layer is set according to the shape and structure of the parts, and each layer of mixture and adhesive is infrared cured after spraying. The infrared wavelength is 900nm and the infrared radiation power is 50W·cm -2 After the binder jet 3D printing is completed, the residual mixed material is recovered by powder suction and can be printed again after sieving;
[0033] Step 3: The printed parts after powder recovery are placed in a degreasing and sintering integrated furnace for sintering. Degreasing + sintering process: room temperature -200℃, 2.5℃ / min; 200℃-200℃, keep warm for 60min; 200-350℃, 1.5℃ / min; 350-350℃, keep warm for 90min; 350-500℃, 1.5℃ / min; 500-500℃, keep warm for 120min; 500-1000℃, 7.5℃ / min; 1000-1400℃, 4℃ / min; 1400-1400℃, keep warm for 90min; 1400-500℃, 10℃ / min; cool with the furnace. HIP gas pressure process: 0-1000℃, 0MPa; 1000-1400℃, 8MPa; then depressurize;
[0034] Step 4: After sintering, the rough parts are double-end surface ground in batches to obtain TiB2-TiN-based cermets. After using the double-end surface grinding machine, the surface parallelism of the tool reaches 0.002mm, the surface roughness can reach up to Ra0.4μm, and the workpiece size deviation is ±0.002mm.
[0035] The mechanical properties of the metal ceramic parts were tested: room temperature hardness was 17.4GPa; bending strength was 726MPa; fracture toughness was 7.4MPa·m 1 / 2At 1000℃, the hardness is 9.7GPa, the flexural strength is 598MPa, and the fracture toughness is 6.1MPa·m 1 / 2 The XRD of the parts prepared by bond spraying + reactive gas pressure sintering showed TiB2, TiN and FCC structural bonding phases. SEM showed that the TiB2 grains were small (average size was 360nm), uniform and dense as a whole, with no obvious pores.
[0036] Embodiment 2: A method for rapidly preparing TiB2-TiN-based cermets by bonding jet 3D printing and SHS, comprising the following steps:
[0037] Step 1: Weigh the binder jet 3D printing raw materials, with a ratio of Ti: 67wt%, BN: 23wt%, CoCrFeMnNiAl: 10wt%. Then place the materials in a double J-blade mixing and vibrating machine with a loading capacity of 70% and a mixing time of 6h. After mixing, a mixture with a coefficient of variation CV of 3.2% is obtained;
[0038] Step 2: Load the mixture and binder into the binder jet 3D printer, the binder content is 40wt% of the premix. The binder ingredients are: epoxy acrylate 70vol%, tripropylene glycol diacrylate 13vol%, pentaerythritol triacrylate 10vol%, 2-hydroxy-2-methyl-1-phenylacetone 2vol%, sodium dodecyl sulfate 3vol%, NaErF4:Yb 3+ 3vol%. The thickness of the mixture and adhesive layer is set according to the shape and structure of the parts. Each layer of mixture and adhesive is infrared cured after spraying. The infrared wavelength is 950nm and the infrared radiation power is 70W·cm -2 After the binder jet 3D printing is completed, the residual mixed material is recovered by powder suction and can be printed again after sieving;
[0039] Step 3: The printed parts after powder recovery are placed in a degreasing and sintering integrated furnace for sintering. Degreasing + sintering process: room temperature -200℃, 3℃ / min; 200℃-200℃, keep warm for 30min; 200-350℃, 2℃ / min; 350-350℃, keep warm for 60min; 350-500℃, 2℃ / min; 500-500℃, keep warm for 90min; 500-1000℃, 10℃ / min; 1000-1400℃, 5℃ / min; 1400-1400℃, keep warm for 60min; 1400-500℃, 10℃ / min; cool with the furnace. HIP gas pressure process: 0-1000℃, 0MPa; 1000-1400℃, 5MPa; then depressurize;
[0040] In step 4, the rough parts after sintering are double-end surface ground in batches to finally obtain TiB2-TiN-based cermets. After using the double-end surface grinding machine, the surface parallelism of the tool reaches 0.002mm, the surface roughness can reach up to Ra0.4μm, and the workpiece size deviation is ±0.002mm.
[0041] The mechanical properties of the metal ceramic parts were tested: room temperature hardness was 17.4GPa; bending strength was 726MPa; fracture toughness was 7.4MPa·m 1 / 2 At 1000℃, the hardness is 9.7GPa, the flexural strength is 598MPa, and the fracture toughness is 6.1MPa·m 1 / 2 SEM showed that the TiB2 grains were coarser (560 nm) than those in Example 1, with more pores, and the TiB2 synthesized by the reaction was largely segregated, affecting the performance of the metal ceramic.
Claims
1. A method for rapidly preparing TiB2-TiN-based cermets based on 3D printing and SHS composite, characterized in that: The method comprises the following steps: 1) Weigh the raw materials of TiB2-TiN-based cermet in proportion, place them in a double J-blade mixing and vibrating integrated machine for mixing, and obtain a bonded jet 3D printing mixture after the mixing is completed; 2) The mixture prepared in step 1) is loaded into a binder jet 3D printer together with a binder, and printing and slicing parameters are set according to the three-dimensional models of parts with different complex shapes and structures, and a TiB2-TiN-based metal ceramic material body is obtained by infrared curing; 3) The TiB2-TiN-based metal ceramic material green bodies obtained in step 2) are transported in batches to a gas pressure sintering furnace to complete degreasing + HIP gas pressure sintering to obtain rough parts; 4) The rough component samples obtained in step 3) are subjected to batch double-end surface grinding and polishing to finally obtain TiB2-TiN metal ceramics with complex shape structures.
2. A method for rapidly preparing TiB2-TiN-based cermets based on 3D printing and SHS composite according to claim 1, characterized in that In step 1), the raw materials include Ti, BN, and CoCrFeMnNiX high entropy alloy, and the mass proportion of each raw material is: Ti: 60-70 wt%, BN: 20-25 wt%, CoCrFeMnNiX: 10-15 wt%.
3. A method for rapidly preparing TiB2-TiN-based cermets based on 3D printing and SHS composite as claimed in claim 2, characterized in that The difference δ of the selected radius of the X element in the CoCrFeMnNiX high entropy alloy is less than 12%.
4. A method for rapidly preparing TiB2-TiN-based cermets based on 3D printing and SHS composite according to claim 1, characterized in that In step 1), the double J-blade mixing and vibrating integrated machine adopts a semicircular rocking block, the vibration amplitude is ≤3°, the blades are double J-shaped, and dual-power drive is used to achieve forward and reverse rotation; the loading capacity of the integrated machine is: 50%≤loading capacity≤80%, and the coefficient of variation CV of the uniformity of the mixture is ≤5%.
5. A method for rapidly preparing TiB2-TiN-based cermets based on 3D printing and SHS composite according to claim 1, characterized in that In step 2), the binder mainly includes the following components in percentage by weight: acrylic resin: 55-85wt%, acrylate reactive diluent: 15-35vol%, photoinitiator: 1-5vol%, up-conversion material: 1-5vol%, the amount of the binder added accounts for 35-45wt% of the mixture, and each layer of the binder is infrared cured after spraying, the infrared wavelength is 800-980nm, and the infrared radiation power is 30-80W·cm -2 .
6. A method for rapidly preparing TiB2-TiN-based cermets based on 3D printing and SHS composite as claimed in claim 5, characterized in that The acrylic resin is selected from at least one of polyurethane acrylate, amino acrylate and epoxy acrylate; the acrylate reactive diluent is selected from at least one of 1,6-hexanediol diacrylate, pentaerythritol triacrylate and tripropylene glycol diacrylate.
7. A method for rapidly preparing TiB2-TiN-based cermets based on 3D printing and SHS composite as claimed in claim 5, characterized in that The photoinitiator is selected from at least one of sodium dodecyl sulfate, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and 2-hydroxy-2-methyl-1-phenylacetone; the up-conversion material is selected from at least one of fluoride, oxide, and oxygen-containing acid salt; the fluoride is at least one of NaYF4, NaErF4, NaGdF4, LuF3, and CaF3; the oxide and oxygen-containing acid salt are at least one of LaPO4, PbWO4, and GdVO4.
8. A method for rapidly preparing TiB2-TiN-based cermets based on 3D printing and SHS composite according to claim 1, characterized in that In step 3), the specific process of degreasing + HIP gas pressure sintering is: room temperature-200℃, 2-3℃ / min; 200℃-200℃, keep warm for 30-60min; 200-350℃, 1-2℃ / min; 350-350℃, keep warm for 60-90min; 350-500℃, 1-2℃ / min; 500-500℃, keep warm for 90-120min; 500-1000℃, 5-10℃ / min; 1000-1400℃, 3-5℃ / min; 1400-1400℃, keep warm for 60-90min; 1400-500℃, 10℃ / min; cooling with the furnace; HIP gas pressure process: 0-1000℃, 0MPa; 1000-1400℃, 5-8MPa; then depressurize.
9. A method for rapidly preparing TiB2-TiN-based cermets based on 3D printing and SHS composite according to claim 1, characterized in that In step 4), after grinding and polishing, the surface parallelism of the parts reaches 0.002mm, the surface roughness can reach up to Ra0.4μm, and the workpiece size deviation is ±0.002mm.
